2013
DOI: 10.1103/physrevc.88.037601
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of ultracold neutron upscattering and absorption in polyethylene and vanadium

Abstract: The study of neutron cross sections for elements used as efficient "absorbers" of ultracold neutrons (UCN) is crucial for many precision experiments in nuclear and particle physics, cosmology and gravity. In this context, "absorption" includes both the capture and upscattering of neutrons to the energies above the UCN energy region. The available data, especially for hydrogen, do not agree between themselves or with the theory. In this report we describe measurements performed at the Los Alamos National Labora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Quasi-bound UCN loaded into the trap could escape on a time scale similar to τ n , which could systematically affect the exponential decay curve and introduce an additional time constant. There are ongoing experimental and theoretical studies of this effect [38][39][40], which has been observed in material and magnetic traps under certain experimental conditions [22,37]. In the current experiment, we remove the population of quasi-bound UCN during and after filling the trap by using a 35.5 × 66.0 cm 2 polyethylene sheet ("cleaner") suspended at the top of the trap (C in figure).…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Quasi-bound UCN loaded into the trap could escape on a time scale similar to τ n , which could systematically affect the exponential decay curve and introduce an additional time constant. There are ongoing experimental and theoretical studies of this effect [38][39][40], which has been observed in material and magnetic traps under certain experimental conditions [22,37]. In the current experiment, we remove the population of quasi-bound UCN during and after filling the trap by using a 35.5 × 66.0 cm 2 polyethylene sheet ("cleaner") suspended at the top of the trap (C in figure).…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Historically the first method of the UCN spectroscopy was the time-of-flight technique [1]. As a direct and universal method of measuring the neutron speed, it has been successfully used in numerous experiments with UCN (see for example [2][3][4][5][6]). …”
Section: Introductionmentioning
confidence: 99%
“…The UCNτ experiment is investigating an 'internal' UCN detection system that uses a vanadium foil lowered into the trap to absorb all surviving UCNs at the end of the storage interval. The activated foil is then raised into a shielded counting enclosure, where the activation is measured by detecting a subsequent coincidence of β and γ particles emitted from the decay of UCN-activated 52 V [206,207]. Such a detector has the advantage of a high detection efficiency and a fast UCN collection time.…”
Section: Ucnτ Experimentsmentioning
confidence: 99%
“…Vanadium is an excellent material for this application, in that 51 V has an isotopic abundance of 99.75%, the absorption cross-section for 4 − m s 1 UCNs is 2700 barn, the UCN upscatter cross-section is two orders of magnitude smaller than the absorption cross-section, and the Fermi potential for natural V is = − V 7 neV F [206]. This last fact ensures that the reflection probability for UCNs on natural V is effectively negligible (below about 5%) for UCN energies greater than 5 neV.…”
Section: Measurement Of the Neutron β-Decay Lifetime With Ucnτmentioning
confidence: 99%